Digital inequalities and U.S. undergraduate outcomes over the first two years of the COVID-19 pandemic - Katz, Vikki S.; Jordan, Amy B.; Ognyanova, Katherine (PLOS ONE, 2025)
The COVID-19 pandemic necessitated major and rapid changes to undergraduate student learning conditions, but the longer-term consequences of those changes have yet to be fully understood. We assess how digital inequality—defined as challenges in accessing or maintaining a broadband internet connection and functional digital devices—affected undergraduates’ advancement toward on-time graduation over the first two years of the pandemic (2020-2022). We utilize survey data from a representative sample of 1,106 undergraduates at Rutgers University-New Brunswick, a public, 4-year university located in New Jersey, USA. Respondents were undergraduates who had been enrolled in full-time student status throughout the first two years of the pandemic. We examine how digital inequality and other sociodemographic factors affected their persistence in full-time student status toward on-time graduation using structural equation modeling. Results show that students with inadequate or inconsistent internet and digital devices developed less remote learning proficiency than their better-connected peers. They were more likely to report having taken incomplete grades in specific courses and/or to have extended their time to graduation. We discuss the implications of these findings for developing digital components to campus emergency planning and for efforts to ensure more equitable learning experiences for undergraduate students in non-emergency periods in the aftermath of the pandemic.